REPRESENTASI BIAS GENDER DAN CIRI INDONESIA (STUDI KASUS:NYI RORO KIDUL DAN GATOT KACA): Gender Bias and Indonesian Trait Representation (Case Study: Nyi Roro Kidul and Gatot Kaca) - Bahaduri, Berti Alia; Gunawan, Peter Rhian; Clara, Beverly (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2024)
Gender Bias and Indonesian Trait Representation (Case Study: Nyi Roro Kidul and Gatot Kaca). Local legend and shadow puppet stories still have place to perform and inspire in Indonesian popular culture. This journal entry discusses two characters’: Nyi Roro Kidul from local lore and Gatot Kaca from the Indonesian Shadow Puppet narrative. These two characters have been represented in popular mediums such as comics, books, movie posters, and an online game. These two characters were chosen to show each gender. The visual samples for the representation are Roro from Ghost School Days comic series, Kadita from Mobile Legends Bang Bang, Nyi Roro Kidul from Kisah Tanah Jawa Book, and Gatot Kaca from Putra Langit comic trilogy, Satria Dewa Movie and Mobile Legends Bang Bang. Social semiotics and questionnaires were the mixed methods to analyze these visuals. The social semiotic method consists of representational, interactive, and compositional meanings. These three meanings are part of the gender construct.  This study's findings are Nyi Roro Kidul illustration was considered the most feminine and has the most Indonesian traits. While Gatot Kaca from Putra Langit was considered the most masculine and Indonesian.